2016
DOI: 10.1155/2016/5893601
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Screening and Grading of Age-Related Macular Degeneration from Texture Analysis of Fundus Images

Abstract: Age-related macular degeneration (AMD) is a disease which causes visual deficiency and irreversible blindness to the elderly. In this paper, an automatic classification method for AMD is proposed to perform robust and reproducible assessments in a telemedicine context. First, a study was carried out to highlight the most relevant features for AMD characterization based on texture, color, and visual context in fundus images. A support vector machine and a random forest were used to classify images according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Most of these studies focused on the grading severity of diseases. Previously published papers claim that a concept of multi-categorical classification was applied to predict AMD progression by using SVM and RF [ 53 ]. Multiclass SVM also worked well in classification of DMR severity [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies focused on the grading severity of diseases. Previously published papers claim that a concept of multi-categorical classification was applied to predict AMD progression by using SVM and RF [ 53 ]. Multiclass SVM also worked well in classification of DMR severity [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…al. 3 Phan et al 5 Burlina et al 29 Accuracy late wet AMD, sensitivity was 59% for 1 year and 60% for 2 years; the specificity was 68% for 1 year and 70% for 2 years. ( Supplementary Table S15, online supplement).…”
Section: Metricmentioning
confidence: 99%
“…By using a robust Haralick set of features (averaged across different displacements and angles) and a machine learning algorithm, we determined the most important texture features and their combinations with intensity features for drusen diagnosis. Finally, instead of using only the green channel as in [37] and [53] where local binary patterns (LBP) features computed in green channel where reported to be the most important features in distinguishing drusen from non-drusen images, we showed that hyper-spectral imaging has the potential to provide the optimal combination of texture and intensity features for drusen ROIs characterization.…”
Section: Discussiomentioning
confidence: 90%